Get hard [videorecording (DVD)] - Ferrell, Will, 1967-; Hart, Kevin, 1979-; Brie, Alison; Nelson, Craig T. (Warner Bros., 2015)
A millionaire is pegged for fraud and sentenced to time in prison. He turns to a criminal friend to help prepare him to go.